Luminescent Thin Films Composed of Nanosized Europium Coordination Polymers on Glass Electrodes. Issue 2 (14th October 2015) - Hasegawa, Yasuchika; Sugawara, Takeshi; Nakanishi, Takayuki; Kitagawa, Yuichi; Takada, Makoto; Niwa, Akitsugu; Naito, Hiroyoshi; Fushimi, Koji
Abstract: Luminescent thin films composed of thermostable lanthanide coordination polymers on glass electrodes were prepared using a novel combination of micelle reactions and electrochemical deposition techniques. The micelle‐encapsulated luminescent polymers were obtained by the polymerization of [Eu(hfa)3 ] (hfa=hexafluoroacetylacetonate) with bridging phosphine oxide ligands in micelles using a redox‐active ferrocenyl‐containing surfactant in water. Films were electrochemically deposited on indium tin oxide coated glass electrodes by potentiostatic polarization of micelle‐encapsulated Eu III coordination polymers. The luminescence properties of the electrochemically deposited films were characterized by measuring their emission spectra, emission lifetimes and emission quantum yields. Abstract : Make a film about it : Luminescent thin films composed of thermostable europium coordination polymers on indium tin oxide glass electrodes were prepared using a novel combination of micelle reactions and electrochemical deposition techniques. The emission spectra, lifetimes and quantum yields of these films were determined.